Vitamin D, immune regulation, the microbiota, and inflammatory bowel disease - Cantorna, Margherita T. (2014)
The inflammatory bowel diseases (IBD) are complex diseases caused by environmental, immunological and genetic factors. Vitamin D status is low in patients with IBD and experimental IBD is more severe in vitamin D deficient or vitamin D receptor knockout animals. Vitamin D is beneficial in IBD because it regulates multiple checkpoints and processes essential for homeostasis in the gut. Vitamin D inhibits IFN-γ and IL-17 production while inducing regulatory T cells. In addition, vitamin D regulates epithelial cell integrity, innate immune responses, and the composition of the gut microbiota. Overall vitamin D regulates multiple pathways that maintain gastrointestinal homeostasis. The data support improving vitamin D status in patients with IBD.